Pengaruh Profitabilitas, Leverage, dan Likuiditas Terhadap Nilai Perusahaan dengan Kebijakan Dividen Sebagai Variabel Moderasi Pada Perusahaan Sub Sektor Makanan dan Minuman Yang Terdaftar di BEI Periode 2018-2022 - Ningsih, Riani Wiliya; Negara, Iwan Kusuma (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This research aims to test and analyze the influence of Profitability, Leverage and Liquidity on Company Value with Dividend Policy as a Moderating Variable in Food and Beverage Sub-Sector Companies Listed on the IDX for the 2018-2022 Period. This research is associative research with a quantitative approach. The population in this research is 22 companies in the Food and Beverage Sub Sector listed on the Indonesia Stock Exchange in 2018-2022. In determining the sample using the Purposive Sampling method, a sample of 12 companies was obtained for 5 years with an analysis of 60 observations. In this research, the panel data regression model is applied using the Random Effect Model (REM) approach, while testing the moderating variables is carried out using MRA (Moderated Regression Analysis) with the EViews 12 program. The test results show that Profitability, Leverage and Liquidity have no effect on company value. Meanwhile, Dividend Policy as a moderating variable is unable to moderate Profitability, Leverage and Liquidity on Company Value.